The influence of cigarette smoking on gingival bleeding and serum concentrations of haptoglobin and alpha 1-antitrypsis - Al-Bayaty, F.H.; Baharuddin, N.; Abdulla, M.A.; Ali, H.M.; Arkilla, M.B.; AlBayaty, M.F. (2013)

(untitled)
The objectives of this study were to evaluate the influence of cigarette smoking on gingival bleeding and serum concentrations of cotinine, haptoglobin, and alpha 1-antitrypsin in Malaysian smokers. A total of 197 male smokers and nonsmokers were recruited for this study. Plaque index, bleeding on probing (BOP), and levels of serum cotinine, haptoglobin, and alpha 1-antitrypsin were evaluated. The data were analyzed using SPSS version 20.0, with the significance level set at alpha < 0.05. Linear regression analyses were performed. The mean cigarette consumption per day was 13.39 +/- 5.75 cigarettes; the mean duration was 16.03 +/- 8.78 years. Relatively low BOP values (26.05 +/- 1.48) and moderate plaque indexes (51.35 +/- 11.27) were found. The levels of serum cotinine (106.9 +/- 30.71 ng/dL), haptoglobin (76.04 +/- 52.48 mg/dL), and alpha 1-antitrypsin (141.90 +/- 18.40 mg/dL) were significantly higher in smokers compared to non-smokers. Multiple logistic regression models for all variables and smokers demonstrated observed differences between BOP, the number of cigarettes per day, and duration of smoking, while serum cotinine, haptoglobin and alpha-1 antitrypsin levels showed no significant differences. Duration of smoking (years) and the cotinine level in serum showed a significant correlation with plaque index. The present analysis demonstrated that the duration of smoking in years, but not the number of cigarettes smoked per day, was associated with reduced gingival bleeding in smokers.